Analisis Efisiensi pada Lembaga Amil Zakat Nasional dengan Pertumbuhan Penghimpunan Zakat Terbaik - Nurul Alifiah Hasan; Rifqi Muhammad (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Purpose: This study analyzes the efficiency of one of the National Amil Zakat Institutions in Indonesia which is the zakat institution with the best zakat collection growth, namely Laznas PPPA Darul Qur'an Foundation. The purpose of this research is to assess the performance of a zakat institution in carrying out its role as a zakat manager. Method: The type of research used is quantitative with a non-parametric approach. The research method in this study is the Data Envelopment Analysis (DEA) method. Results: Based on the results of data processing in 2017-2020 Laznas PPPA Daarul Qur'an financial reports, these findings indicate that Laznas PPPA Daarul Qur'an experienced inefficiency in 2017 and 2018 with an inefficiency level of 95,63% in 2017 and there was an efficiency improvement with a score of 98.95% in 2018. Until finally in 2019 and 2020 Laznas PPPA Daarul Qur'an is at the optimal efficiency value of 100%. Implication: The existence of this research is expected to provide an overview to the community, as well as a reference for other zakat management organizations in assessing the performance of a zakat institution.Novelty: The previously inefficient conditions continue to be addressed by making various efforts through programs to maximize the management of zakat.